Fistula Coronary and Coronary Steal Syndrome: A Case Report - Saskia Handari; Puspa Lestari (Cardiovascular and Cardiometabolic Journal, 2022)
Background: A coronary artery fistula (CAF) is an aberrant vascular contact of coronary arteries with cardiac chambers or any section of the pulmonary or systemic circulation, which accounts for 0.3% of congenital heart disorders. CAFs have been observed to be as common as 0.9% at computed tomographic (CT) angiography, which is greater than the previously estimated prevalence of 0.002 – 0.3% at invasive angiography. Case Summary: A 76-year-old woman reported with repeated episodes of chest pain. A considerable diameter of fistula from the proximal LAD and proximal RCA to the MPA was discovered on CT angiography, which could be the cause of coronary steal syndrome. Microflex10 7 mm/22 cm was used to perform coil embolization at the proximal RCA. After the procedure, the patient had no more chest pain. Discussion: CT angiography is usefsul for determining coronary architecture and guiding therapeutic intervention. CAF data was gathered during pre- and post-procedural CT angiography evaluations. Keyword: Fistula coronary, coronary steal syndrome, CCTA, percutaneous coil embolization